Factors affecting the concept of an ideal mate among selected young adult teaching staff in the University of the Philippines - Felipe, Jodelle Kristine D.; Infantado, Marie Grace; Sarmiento, Johanna Vaylen M. (Quezon City College of Home Economics, University of the Philippine Diliman, 2014)
ABSTRACT Havighurst?s (1953) Developmental Task for Young Adulthood states that young adults are of age in which they are expected to select a mate, marry, and establish a family of their own (p.257). In the Philippines, this process of mate selection is evident during courtship (Torres, 2002). Choosing a potential partner entails several social, cultural, and psychological factors. Thus, it is not only interesting but also essential to know such factors as these reflect the kind of values that people in a society prioritize (Capistrano, 2003; Zulueta, 1980; Bandalaria, 1995; Belen, 2007). Most Mate Selection theories particularly about sex differences are built on the evolutionary and socio psychological perspectives (Clark, Dover, Geher, & Presson, 2005, p. 181). Hence, this study made use of the Filter Theory, in which the potential mate is sorted out from a pool of eligibles upon passing through cultural, sociological, and psychological filters. The research aimed to shed light on the characteristics of an ideal mate and the factors affecting its formation using sex difference as a variable among selected young adult instructors of the University of the Philippines, Diliman. A survey questionnaire which included an open-ended section wherein the participants were asked to enumerate the characteristics they desire in their ideal mate and a19-item Likert scale based on Geher and Clark (2005) and an interview were the tools used for data collection. Forty (40) participants (20 males and 20 females) from different colleges within the university participated on the survey, whereas 20 participants (10 males and 10 females) from the said sample proceeded to the interview. Factor Analysis and One-Way ANOVA were used to analyze the information obtained from the participants. The data gathered from the respondents proved that males and females differ not only in the characteristics that they look for in a mate but also in the reasons and factors that influence them to think and consider their preferred traits. These details are then used to form a general trend that describes the overall desired traits by the sample at the given place and time. Finally, aside from adding relevant information to Philippine literature, the study provided useful data to FLCD courses particularly those involving values formation and young adult social development.
Thesis (B.S. Family Life and Child Development)--University of the Philippines Diliman.
Keywords: Mate selection -- Philippines